Soft robotics : technology for the future - Hein, Htet Aung (2018)
Soft Robotics becomes popular topic for new researches all around the world recently for its boundless potentials in numerous applications. Technological developments in smart materials, smart actuators, soft sensors, smart control systems and advanced manufacturing technologies are driving factors for soft robotics field. Due to its life-like capabilities and advantages, soft robots are expected to replace current robotic systems in near future. In this report, simple test rig is constructed, and its outcomes and advantages are discussed. Prospects and future improvements are also suggested at the end of report.